Cerebral vasoconstriction after carotid endarterectomy. Issue 5 (6th June 2018) - Fitas, Diogo; Carvalho, Marta; Castro, Pedro; Abreu, Pedro; Moreira, Goreti; Santos, Rosa; Azevedo, Elsa
Abstract : Carotid endarterectomy carries the risk of several complications. We report a 55-year-old woman with recurrent cerebral vasoconstriction postoperatively. She had bilateral high-grade internal carotid artery stenosis and underwent right endarterectomy because of transient left-sided sensory symptoms. She developed a reperfusion syndrome with severe right-sided headache, right frontotemporal oedema and increased velocities in transcranial Doppler ultrasound. Given her gradual increase of velocities and Lindegaard index, together with fixed left sensory and motor deficits, we performed CT angiography, which suggested cerebral vasoconstriction syndrome. A subsequent left carotid endarterectomy triggered a similar cerebrovascular response. We highlight the need for continuous monitoring of cerebral haemodynamics following carotid endarterectomy.